Evaluation of the Depth of Cure by Microhardness of Bulk-Fill Composites with Monowave and Polywave LED Light-Curing Units - Socratis Thomaidis; Dimitris Kampouropoulos; Maria Antoniadou; Afrodite Kakaboura (Applied Sciences)
This study aimed to evaluate the depth of cure (DoC) of bulk-fill composite resins, measured by the bottom-to-top Vickers microhardness ratio, using different light-curing units (LCUs): single-wave LED, polywave LED, and halogen. Six bulk-fill composites—Tetric EvoCeram Bulk Fill, X-tra base, SonicFill, Venus Bulk Fill, SDR, and Filtek Bulk Fill—were tested. Four LCUs, including one halogen (Elipar Trilight) and three LEDs (Demi Ultra, Valo, and Bluephase style), were employed for polymerization. Vickers hardness measurements were taken at depths of 1 mm to 5 mm. One- and two-way ANOVA (α = 0.05) were used for data analysis. The results revealed significant differences in microhardness and microhardness ratios among the composites at depths of 4 mm and beyond, depending on the LCU used. It was observed that most bulk-fill composites showed an adequate DoC up to 4 mm, but the effectiveness varied with different LCUs. Importantly, polywave LED LCUs did not exhibit a superior advantage in achieving depth of cure compared to monowave LED LCUs for composites containing multiple photoinitiators. These findings suggest that while several factors affect the DoC, the type of LCU plays a crucial role, and polywave LEDs may not offer additional benefits over monowave LEDs.